RECONSTRUCTION OF THE LOCAL GOVERNMENT MODEL BASED ON THE CONCEPT OF THE FOUNDING FATHERS AND THE 1945 CONSTITUTION JUNCTO THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA TOWARS MODERN LOCAL GOVERNMENT - Chanif Nurcholis; Sri Wahyu Kridasakti (Faculty of Law, Universitas Sebelas Maret, 2018)
The model of local governance has always changed since Indonesian independence, namely centralized and decentralized model. According to Law Number 23 of 2014 and Law Number 6 of 2014 the model of regional government returned to the traditional conservative centralized model. This model is not in accordance with the model of local government initiated by the founding fathers and norms of Article 18 of the 1945 Constitution and norms of Article 18, 18A and 18B of the 1945 Constitution of the Republic of Indonesia (after amendment). According to this problem, text research is conducted. The purpose of this study is to compare the models of local governance practiced since the colonial era until now with the model of local government conceived by the founding fathers and the 1945 Constitution. This research is a normative research with content analysis method. The result of the research is that the current system of local government deviates from the founding father conception (Muhammad Yamin, R. Soepomo, and Mohammad Hatta) and the 1945 Constitution. The conception of local government according to the founding fathers and the 1945 Constitution is modern urban decentralized regional government while the regional and village governments are regulated by Law Number 23 of 2014 on The Local Government juncto Law Number 6 of 2014 on The Village is a conservative and traditionally centralized of the local governance model.